Enhancing Speaking Skill and Critical Thinking by Using Socratic Method at Senior High School Students' of Al-Fath Modern Islamic Boarding School - Fhadillah Dhuha; Sondang Manik (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
Answering questions is considered more popular than asking questions. Socratic questioning is a method of learning by conversation or discussion where students are faced with some eccentric problems that create a series of questions. This research uses a qualitative descriptive design by collecting data from documents, observations and interviews. Then the data is analyzed using qualitative data analysis. Miles and Huberman show the theory about collecting data analysis which includes data collection, data display, and conclusion drawing/verification. In Socratic Method develops the expansion of cognitive and analytical abilities, Socratic method could be an appropriate way to teach English. This method involves asking questions in a way that allows everyone to share ideas and also helps to create a positive environment for learning. Questioning where the types of questions most widely used by students are questions that explore information, reasons, evidence, and causes. Questions for clarification appeared. Questions about viewpoints and perspectives appear, followed by questions that explore assumptions, questions about questions and the least common question is questions about implications/consequences. As a way to train critical thinking skills, speaking and critical thinking skills are very important in the learning process that requires both skills and analytical process while students have lack of grammar and vocabulary, facts and evidence. How to make students enjoy learning speaking that would be a challenge for the writer when he taught at senior high school students' of Pondok Pesantren Modern Al-Fath. Another thing the result of the research: theoretically could become a new way in practicing speaking by using Socratic Method especially for critical thinking skills in English.